Consumption of antibacterials in three hospitals in Santiago de Cuba in the period 2019-2020 - Maraelys Morales-González; Clara A. Zúñiga-Moro; Oneyda Clapé-Laffita; Elianis García-Díaz; Tania Quintana-Hernández; Niurka M. Dupotey-Varela; Maryenis Rodríguez-Alfaro; Lourdes Serpa-Hernández (GarVal Editorial Ltda., 2022)
Context: Infections by multiresistant bacteria increase the risk of therapeutic failure, increasing hospital stay, costs and mortality. This determines the use of more expensive antibacterials with a broader spectrum, which leads to a high consumption at the hospital level, which increases bacterial resistance. Aims: To characterize the consumption of antibacterials in three hospitals in Santiago de Cuba. Methods: A descriptive and cross-sectional study of consumption was carried out. The consumed units, anatomical, therapeutic, and chemical classification, route of administration and price were analyzed for each antimicrobial. The defined daily dose (DDD)/100 beds/day and the cost of antibacterials for systemic use were determined. Descriptive statistics were used. Results: The most used antibacterial in both years (2019 and 2020) was ceftriaxone (12.6% and 26.9%). The most used group was J01D (39.5% and 44.8%), mainly parenteral via. In 2019 they presented higher DDD/100 beds/day: gentamicin (38.74 in the General Hospital and 20.20 in the Maternal Hospital) and ciprofloxacin (31.51 in the General Hospital and 15.00 in the Oncology Hospital); and in 2020 it was cefazolin (41.42 in General Hospital), ciprofloxacin (17.73 in Oncology) and gentamicin (26.99 in Maternal). The highest total costs were for ciprofloxacin and ceftriaxone. Conclusions: The increase in consumption evidenced the need to update therapeutic policies and validation of prescriptions for this group of drugs.